OLYMPIC SPORTS IN SUMMER OLYMPIC GAMES - LEUCIUC Florin-Valentin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The Olympic Program has known a sinuous evolution over its 100 years of existence, marked by periods of decline, stagnation or progress, this last one being its main characteristic after 1948. The importance of the Olympics determined some countries to adopt a strategy regarding their participation in various sports, in order to obtain medals. Thus, some countries became "expert"in one sample contest or another, getting a "monopoly" of certain Olympic Sports